2011
DOI: 10.1001/jama.2011.1471
|View full text |Cite
|
Sign up to set email alerts
|

Referral to an Extracorporeal Membrane Oxygenation Center and Mortality Among Patients With Severe 2009 Influenza A(H1N1)

Abstract: For patients with H1N1-related ARDS, referral and transfer to an ECMO center was associated with lower hospital mortality compared with matched non-ECMO-referred patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
559
5
27

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 769 publications
(606 citation statements)
references
References 45 publications
15
559
5
27
Order By: Relevance
“…Several reports describe cases of influenza A (H1N1)-associated acute respiratory distress syndrome requiring extracorporeal membrane oxygenation (ECMO) for severe hypoxemia refractory to conventional treatment [1][2][3][4][5][6]. However, uncertainty regarding the appropriate indication for ECMO in these patients still remains [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports describe cases of influenza A (H1N1)-associated acute respiratory distress syndrome requiring extracorporeal membrane oxygenation (ECMO) for severe hypoxemia refractory to conventional treatment [1][2][3][4][5][6]. However, uncertainty regarding the appropriate indication for ECMO in these patients still remains [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…2 The United Kingdom ECMO cohort study showed an approximate 50% reduction in mortality in those referred for ECMO during the same pandemic. 3 These studies are in contrast to the conclusion of the France REVA-SRLF H1N1 Registry. 4 In that study, 103 patients received ECMO, and 52 patients in the cohort were propensity matched to non-ECMO patients.…”
mentioning
confidence: 89%
“…2 Dans une autre étude de cohorte d'ECMO réalisée au Royaume-Uni, on a observé une réduction d'environ 50 % de la mortalité chez les patients référés pour un traitement à l'ECMO pendant la même épidémie. 3 Ces études vont à l'encontre de la conclusion du registre français REVA-SRLF H1N1. 4 Dans cette dernière étude, 103 patients ont reçu un traitement à l'ECMO, et 52 patients de la cohorte ont été appariés selon les scores de propension à des patients ne recevant pas d'ECMO.…”
unclassified
“…The conventional ventilation versus ECMO for severe adult respiratory failure (CESAR) trial first reported a significant improvement in 6 months disability‐free survival in the ECMO group, when compared to conventional ventilation patients 5. Since then, several studies have shown the effectiveness of ECMO for influenza A (H1N1)‐related severe acute respiratory failure in 2009–2010 6, 7. Following the pandemic of influenza A (H1N1), however, few reports have explored the benefits of ECMO 8.…”
Section: Introductionmentioning
confidence: 99%